Gait Analysis by the Severity of Gait Disturbance in Patients with Compressive Cervical Myelopathy - Tatsuo Makino; Kei Watanabe; Tatsuki Mizouchi; Takaaki Urakawa; Masayuki Ohashi; Hideki Tashi; Keitaro Minato; Yuki Tanaka; Hiroyuki Kawashima (Spine Surgery and Related Research, 2023)
Introduction: Gait disturbance due to compressive cervical myelopathy has been previously described. However, data on how gait disturbance varies with the degree of lower extremity motor impairment are limited. Therefore, we investigated the characteristics of gait analysis based on severity and determined how gait disturbance progresses in compressive cervical myelopathy. Methods: We enrolled 44 patients (32 men and 12 women; mean age, 65.0 years) out of 108 consecutive patients with compressive cervical myelopathy who underwent spinal cord decompression surgery in our hospital. The exclusion criteria were inability to gait and complications affecting gait. Twenty-two patients with Japanese Orthopaedic Association scores 1 or 2 for lower extremity motor functions were assigned to the severe group, and 22 patients who scored 3 or 4 were assigned to the moderate group. Gait analysis was performed preoperatively using a long thin-type sensor sheet, and 25 healthy volunteers were assigned to the control group. Results: Stride length, swing phase, and gait speed decreased whereas step angle, stance phase, and double support duration increased as myelopathy progressed. Step width was significantly larger in the severe group than in the moderate and control groups. The cutoff values based on severe myelopathy with the inability to ascend or descend stairs without support were 60% for the stride length percentage of body height and 100 cm/s for gait speed. Conclusions: Decreases in stride length, swing phase, and gait speed and increases in step angle, stance phase, and double support duration are compensatory changes as cervical myelopathy progresses. Step width is a compensatory change that is not significantly altered in moderate myelopathy but increases when gait becomes affected, such that the patient cannot ascend or descend stairs without support.